2018
DOI: 10.1002/adfm.201800502
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Acid Stability of Polypyrrole‐MoS4: A Highly Selective and Efficient Scavenger of Heavy Metals Over a Wide pH Range

Abstract: displays high acid stability and excellent uptake for heavy metal ions such as Hg 2+ , Ag + , Cu 2+ , and Pb 2+ . The different maximum adsorption capacities (q m ) for Cu 2+ , Pb 2+ , Hg 2+ , and Ag + depend on the various binding modes arising from the different thiophilicity of these metal ions. The removals of Ag + and Pb 2+ reach >99.6% within 5 min, and for highly toxic Hg 2+ , >98% removal achieves at 1 min. At strong acid limit, the exceptional q m (Ag + ) of 725 mg g −1 places the MoS 4 -Ppy at the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 75 publications
6
45
2
Order By: Relevance
“…Similar XRD patterns of Pb(II)-adsorbed MoS 2 nanocomposite suggesting the formation of PbMoO 4 after adsorption have also been reported in the literature. 27,70 The morphological changes after adsorption were studied using SEM and EDX mapping (Figure 12). SEM images of Cd(II)-adsorbed MoS 2 /SH-MWCNT nanocomposite exhibited CdMoO 4– x S x and CdS NPs besides MWCNTs (Figure 12a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Similar XRD patterns of Pb(II)-adsorbed MoS 2 nanocomposite suggesting the formation of PbMoO 4 after adsorption have also been reported in the literature. 27,70 The morphological changes after adsorption were studied using SEM and EDX mapping (Figure 12). SEM images of Cd(II)-adsorbed MoS 2 /SH-MWCNT nanocomposite exhibited CdMoO 4– x S x and CdS NPs besides MWCNTs (Figure 12a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the past, extensive studies have been reported to unravel the scopeo fs uch functional materials as activated porous carbon, [5] zeolites, [6] silica particles, [7][8][9][10][11][12][13] graphene oxide, [14,15] metals or metal oxides, [16,17] natural minerals [18][19][20] etc. as adsorbents for remediationo fm etal ions from water.T he search for new and efficient adsorbentsh as prompted the design and synthesis of functional polymers, [21][22][23][24][25][26][27] metal organic frameworks, [28][29][30] polymeric composites [31][32][33] and biohybrids. [34] Nev-ertheless, the problem of low adsorption capacity of these materials stillr emains ac hallenge due to lack of synthetic methods which favor modulations in the physicalp roperties and surfacec hemistry.I tm eanst hat except high surface area the designeda dsorbent should possess functional electron-rich groups on thes urface, whichw ill have strongi nteractionw ith metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional materials used for selenium capture, porous polymer networks (PPNs) have the potential to meet both the cost and removal efficiency requirements. Although amorphous, they can achieve low-cost, facile, and large-scale syntheses. Networks constructed from covalent bonds will also allow for high water stability of the PPN, making them suitable for various applications .…”
Section: Introductionmentioning
confidence: 99%